Method for modeling of near-bottom longlines - Victor I. Gabruk; Ludmila A. Gabruk; Vasily V. Kudakaev; Kseniia A. Belova (Известия ТИНРО, 2017)
Modeling technique for horizontal near-bottom longlines is presented. An example of this technique application for re-equipment of currently used bottom longlines to the near-bottom longlines is considered. Recommendations are given on choice of the buoys buoyancy, the anchor weight, and the weights for rigging of the near-bottom longline.